PHOTOSYNTHESIS, RESPIRATION AND GROWTH RATE OF СHLAMYDOMONAS REINHARDTII ON EXOGENIC ETHANOL APPLICATION - С. С. Степанов; О. К. Золотарьова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Aim. The aim of the present work was studying the effect of ethanol on the rate of photosynthesis, respiration and productivity of Chlamydomonas reinhartdii. Methods. The amount of chlorophyll (Chl) was estimated photometrically. The rate of biomass accumulation was estimated by changes in packed cell volume. The rate of photosynthesis, maximum intensity of respiration and dark respiration was determined by infrared gas analysis. Results. In the presence of ethanol growth of culture in the terms of packed cell volume is inhibited, also the accumulation of Chl in cell culture is reduced and cell death is observed both in the light and in the dark. This is accompanied by decreasing pH of the culture medium from 7.2 to 3.5. The intensity of dark respiration is doubled after the addition of 50 mM ethanol to the culture medium. The rate of photosynthesis is reduced in the presence of 50 mM ethanol on 25% compared with the control. Conclusions. There were made a conclusion that the cause of growth inhibition of C. reinhartdii was incomplete oxidation of ethanol, resulting reduction of pH in the medium by a few units.